Ribonucleoprotein Transfection for CRISPR/Cas9‐Mediated Gene Knockout in Primary T Cells. (18th October 2018) - Oh, Soyoung A.; Seki, Akiko; Rutz, Sascha
Abstract: CRISPR/Cas9 has enabled the rapid and efficient generation of gene knockouts across various cell types of several species. T cells are central players in adaptive immune responses. Gene editing in primary T cells not only represents a valuable research tool, but is also critical for next generation immunotherapies, such as CAR T cells. Broad application of CRIPSR/Cas9 for gene editing in primary T cells has been hampered by limitations in transfection efficiency and the requirement for TCR stimulation. In this article, we provide a detailed protocol for Cas9/gRNA ribonucleoprotein (RNP) transfection of primary mouse and human T cells without the need for TCR stimulation that achieves near complete loss of target gene expression at the population level. This approach enables rapid target discovery and validation in both mouse and human primary T cells. © 2018 by John Wiley & Sons, Inc.